The Effects Of Tannic Acid On Physicochemical, Barrier, And Mechanical Properties Of Bovine Gelatin Films - Mohd Shafullah, Farah Nabila (Universiti Sains Malaysia, 2021)
The main objective of this study is to evaluate the effect of tannic acid on the physicochemical, barrier, and mechanical properties of the bovine gelatin films. The morphology, color, water solubility, mechanical properties, and water vapor permeability (WVP) of the films were investigated. Glycerol was added which act as a plasticizer. The findings of this study showed that there were increase (p > 0.05) in the mechanical properties of the films, where tensile strength (TS) was increased from 2.85 MPa to 10.61 MPa and elongation at break (EAB) was increased from 226.09% to 400.99%.